Effectiveness of Using Hollow as Column Formwork Amplifier Compared with Wood Beam - I Wayan Suasira; I Made Tapayasa; I Ketut Sutapa; I Made Anom Santiana (Pusat Penelitian dan Pengabdian kepada Masyarakat (P3M) Politeknik Negeri Bali, 2020)
In terms of cost utilization, formwork is the largest cost component in concrete work on a building project. The cost for formwork is about 40-60% [6] of the cost of concrete work or about 10% of the total cost of building construction. With two methods of formwork i.e. conventional and half system formwork, the authors want to know the comparison of which formwork method is best in the aspect of cost savings, and the execution time for the formwork of columns on the Standard Villa project. From 2 (two) methods proposed then it is chosen the second method; that is formwork column with method of half system as best alternative. The savings can be done from the first method to the second method as much as 26.17%, while in terms of savings time that can be done with method 2 is equal to 5% of method 1